APLIKASI SISTEM INFORMASI PELAYANAN PUSKESMAS BERBASIS ANDROID - Immanuel Pierre Luigi Sitorus (Sekolah Tinggi Teknologi Informasi NIIT, 2021)
Online Health Services at this time have become a mass phenomenon in all segments of society. The health service application is not always about consulting a doctor but also about ordering a room or buying medicine, the Puskesmas service sees that it is difficult to maintain health during a pandemic or to avoid spreading the virus. The manual system causes the work obtained to be deemed less fulfilling because the entire process depends on human resource factors, which means that the percentage of errors in the human resource segment is quite high and is detrimental to the Puskesmas manager. The method used is the System Development Life Cycle (SDLC), starting from the planning, analysis, application design, and system implementation phases and producing computerized and integrated cellular applications that will immediately generate data and bookkeeping reports which are of course needed by the health center so that services Puskesmas can be more controlled and more faster.